Analisis Analisis Pisikologi Sastra Tokoh Utama Dalam Cerpen Bahasa Bali Stri Ngarania Apuy Padania Karya I Made Suarsa - Nurrohmah, Siti; Sulibra, I Ketut Ngurah; Puspawati, Luh Putu (Dharma Sastra : Jurnal Penelitian Bahasa dan Sastra Daerah, 2026)
This literary psychology analysis examines the main character in the Balinese short story "Stri Ngarania Apuy Padania" by I Made Suarsa. This study aims to identify and describe the psychological condition of the main character, I Gde Sadia, who experiences inner conflict based on Sigmund Freud's psychoanalytic theory, specifically focusing on the Id, Ego, and Superego. This short story was chosen for its strong narrative and complex character characteristics, as well as its relevance to Balinese society. This research uses a qualitative approach with a descriptive method to analyze the data. Data collection was carried out by repeatedly reading the short story, translating it from Balinese to Indonesian, and noting important information. The results of the analysis are presented informally to facilitate reader comprehension The research findings show the manifestation of the Id, Ego, and Superego within the character of I Gde Sadia. The Id aspect is seen in his sexual urges that drove him to have an affair and impregnate Ngatiem. The Ego aspect is indicated by I Gde Sadia's actions of abandoning his responsibilities as a husband and teacher to fulfill his personal pleasures, including living with his mistress. The Superego aspect is described through I Gde Sadia's deep regret for his actions after all the destruction befell him, showing an awareness of good and bad values. The conclusion of this study provides an overview of the inner turmoil and psychological conflicts experienced by the main character in the short story.